Schubert Studies - Newbould, Brian (Aldershot Ashgate, 1998)
Schubert Studies comprises eleven essays by renowned Schubert scholars and performers. The volume sheds light on certain aspects of Schubert's music and biography which have hitherto remained relatively neglected, or which warrant further investigation.Musical topics include analyses of tempo conventions, transitional procedures and rhythmic organization. There are reassessments of several works, using autograph research, performing experience and other approaches; while assumptions as to the extent of Schubert's influence on later Czech composers are also brought into question.Concerns with aspects of Schubert's biography, in particular the social and musical circles in which he moved, come under examination in several essays. The final two chapters deal specifically with the composer's relationships with women, and the psychological and physiological illnesses from which he suffered.Each of the essays here charts new and existing evidence to provide fresh perspectives on these aspects of Schubert's life and music, making this volume an indispensable tool for scholars concerned with his work.Meer ?
Schubert's tempo conventions / Clive Brown -- Schubert's transitions / Susan Wollenberg -- Schubert's string and piano duos in context / Elizabeth Norman McKay -- 'Am Meer' reconsidered: strophic, binary, or ternary? / Edward T. Cone -- Schubert's 'Great' C major Symphony: the autograph revisited / Brian Newbould -- 'Biding his time' – Schubert among the Bohemians in the mid-nineteenth century / Jan Smaczny -- Architecture as drama in late Schubert / Roy Howat -- Schubert's piano sonatas: thoughts about interpretation and performance / András Schiff -- Schubert and the Ungers: a preliminary study / Peter Branscombe -- Schubert's relationship with women: an historical account / Rita Steblin -- Adversity: Schubert's illnesses and their background / Peter Gilroy Bevan
Includes a table of contents, list of plates, an index of Schubert's works and a general index
Keywords: Schubert, Franz -- 1797-1828; 19th Century (1801-1900); Composer; Biography; Musical analysis; Vienna (Austria)